Music teacher in preschool of new formation: technological aspects (Pedagogy of Higher and Secondary Education, 2013)
Shut M. M. Music teacher  in preschool of new formation: technological aspects.In the article the professional requirements to modern music teacher in preschool educational establishment are systematized and the list of modern professional competencies is justified.
Keywords: music teacher; professional requirements; competence